Plan de marketing estratégico para fortalecer el posicionamiento del Hotel “Sara Espíndola” de la ciudad de Tulcán - Ojeda Delgado, Evelin Katherine (2016)
This project has as main purpose to design a marketing plan to improve and strengihen the position of the hotel "Sara Espindola”. Taking advantage of opportunities in the environment and comparative advantages of the hotel, to generale competitive advantages. This research work is based on three chapters systematically processed, which has identified the object processing because the positioning of the hotel "Sara Espindola” city of Tulcan is low. Chapter 1 is the theoretical foundation developed based on the research variables and thus formulate a scientific theoretical framework, in a coordinated and systematic manner. In Chapter 1 the methodological framework in which the research methodology is developed to be used for the diagnosis of the current situation of the hotel "Sara Espindola” in their internal and external factors, diagnosis market was conducted using primary sources detailing which they have provided relevant information to later be analyzed in depth and thus seek to improve and solve problems in order to strengthen the positioning of the hotel which develop in the later chapter. then concluding with Chapter MI where the proposal to solve the problem hotel "Sara Espindola” following a systematic process which lies im developing marketing objectives, marketing strategies, plan of action and follow-up stable and control of the above. Finally we conclude with the results of research and recommends running this research work for the development and strengthening of the hotel "Sara Espindola”